2012
DOI: 10.1016/j.ajhg.2012.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Gene-Centric Meta-analysis across 32 Studies Identifies Multiple Lipid Loci

Abstract: Genome-wide association studies (GWASs) have identified many SNPs underlying variations in plasma-lipid levels. We explore whether additional loci associated with plasma-lipid phenotypes, such as high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), total cholesterol (TC), and triglycerides (TGs), can be identified by a dense gene-centric approach. Our meta-analysis of 32 studies in 66,240 individuals of European ancestry was based on the custom ∼50,000 SNP genotyping array… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
186
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 227 publications
(192 citation statements)
references
References 74 publications
6
186
0
Order By: Relevance
“…Greater than 150 lipid-associated loci have been discovered using genome-wide association studies (GWASs) mainly based on individuals of European ancestry ( 1,2 ). The number of variants discovered and the power to detect variants of lower allele frequency and effect size is directly proportional to the number of participants in the study, demonstrated by the success of gradually larger meta-analyses ( 1 ).…”
Section: African American Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Greater than 150 lipid-associated loci have been discovered using genome-wide association studies (GWASs) mainly based on individuals of European ancestry ( 1,2 ). The number of variants discovered and the power to detect variants of lower allele frequency and effect size is directly proportional to the number of participants in the study, demonstrated by the success of gradually larger meta-analyses ( 1 ).…”
Section: African American Meta-analysismentioning
confidence: 99%
“…SNPs were specifi cally selected from African HapMap samples to be included on the array to ensure coverage of African populations ( 9 ). Results of genetic associations with total cholesterol (TC), LDL cholesterol (LDL-C), HDL cholesterol (HDL-C), and TG concentrations in European-derived cohorts using the IBC array, as well as meta-analysis of multi-ethnic cohorts, have been published ( 2,6 ). Follow-up replication of signals with P < 10 Ϫ 5 from the discovery cohort in African…”
Section: African American Meta-analysismentioning
confidence: 99%
“…A recent meta-analysis has shown that the association between rs1799884 and type 2 diabetes varies according to ethnic populations and could be more important among Caucasians than among Asians (Fu et al 2013). In a large-scale gene-centric meta-analysis, the intronic SNP rs2070971 within GCK gene was associated with plasma TG concentrations (Asselbergs et al 2012). …”
Section: Discussionmentioning
confidence: 99%
“…For C/C homozygotes, low CHO intakes were associated with an increase in plasma TG concentrations, whereas when CHO intakes were high, they had the greatest decrease in their plasma TG concentrations following the fish oil supplementation of all genotype groups. The SNP rs741038 is an intronic SNP with no potential regulatory impact and is not in LD with rs1799884 or rs2070971 which have been associated previously with plasma TG levels, fasting glucose and/or type 2 diabetes risk (Asselbergs et al 2012;Holmkvist et al 2008;Sotos-Prieto et al 2013;Webster et al 2009;Hu et al 2010;Wang et al 2013). However, it is possible that rs741038 is in LD with other unknown functional SNPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation